Cognitive Wi-Fi 2.0 networks:future intelligent WLAN - Chun-gang YANG; Chao XU; Min SHENG; Jian-dong LI; Hong-yan LI (Tongxin xuebao)
One typical deployment scenario was described and several key techniques including channel bonding were introduced.More importantly,a two-tire dynamic spectrum access model was formulated from both the economic and technologic perspectives.In addition,a variety of dynamic resources sharing schemes were summarized.Furthermore,classic game theoretic models were discussed and consequently strategic design of dynamic spectrum access and intelligent network selection were introduced.Finally,a spectrum sharing scheme was proposed and the future of cognitive Wi-Fi 2.0 networks was looked to.